Diversity of Bats (Chiroptera) in the Cimaung Cave Area, Tasikmalaya Regency - Muhtar, Epi Nurul Bariyah; Hernawati, Diana; Chaidir, Diki Muhamad (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Bats are the only mammals that can fly and belong to the order Chiroptera. Chiroptera consists of two suborders, namely Yangochiroptera and Yinpterochiroptera. This study aims to describe environmental factors and the diversity of bat species in the Cimaung Cave area. This research method is a quantitative descriptive research method with an exploratory approach, photo documentation, and data collection techniques using direct sweeping and a mist-net. The stations were used based on several existing zones, namely station 1 (Light Zone), station 2 (Dim Zone), and station 3 (Dark Zone). The results of research on bats found in Cimaung Cave belong to three families (Rhinolophidae, Hipposideridae, and Vespertlionidae) and four species (R. borneensis, R. affinis, H. larvatus, and M. australis). The results of the calculation of the ecological index of bats in the Cimaung cave area include the ShannonWeiner diversity index of 1.19 (moderate), the Krebs density index of 1.98 (very rare), the Simpson dominance index of 0.35 (moderate), the Krebs uniformity index of 0.86 (high) and the Magurran species richness index of 0.42 (low). Information on bat diversity in Cimaung Cave can be used as a basis for research development and utilization in the future. In addition, the presence of bat species in Cimaung Cave can also be used as a reference for education, conservation, and identification activities. As well as the utilization of the indirect economic value of bats, namely as plant pest controllers and guano providers as organic fertilizers.